Developing and trialling a school-based ovulatory-menstrual health literacy programme for adolescent girls: A quasi-experimental mixed-method protocol - Roux, Felicity; Burns, Sharyn; Chih, Hui Jun; Hendriks, Jacqueline (2019)
© Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ. Introduction A review of international and Australian school-based resources suggests that teaching of the ovulatory-menstrual (OM) cycle is predominantly couched in biology. A whole-person framework that integrates spiritual, intellectual, social and emotional dimensions with the physical changes of the OM cycle is needed to facilitate adolescent OM health literacy. This paper describes the protocol for a study that aims to develop and trial an intervention for adolescent girls aged 13-16 years that enhances positive attitudes towards OM health coupled with developing skills to monitor and self-report OM health. These skills aim to foster acceptance of the OM cycle as a 'vital sign' and facilitate confident communication of common OM disturbances (namely, dysmenorrhoea, abnormal uterine bleeding and premenstrual syndrome), which are known to impact school and social activities. Methods and analysis Phase I will comprise a Delphi panel of women's health specialists, public health professionals and curriculum consultants and focus groups with adolescent girls, teachers and school healthcare professionals. This will inform the development of an intervention to facilitate OM health literacy. The Delphi panel will also inform the development of a valid and reliable questionnaire to evaluate OM health literacy. Phase II will trial the intervention with a convenience sample of at least 175 adolescent girls from one single-sex school. The mixed-method evaluation of the intervention will include a pre-intervention and post-intervention questionnaire. One-on-one interviews with teachers and school healthcare professionals will expand the understanding of the barriers, enablers and suitability of implementation of the intervention in a school-based setting. Finally, focus groups with purposively selected trial participants will further refine the intervention. Ethics and dissemination The study findings will be disseminated through local community seminars, conferences, peer-review articles and media channels where appropriate. The Curtin University of Human Research Ethics Committee has approved this study (approval HRE2018-0101). This project is registered with the 'Australian and New Zealand Clinical Trials Registry'. Trial registration number ACTRN12619000031167; Pre-results.